AB0335 The relationship between joint mobility and upper limb function in boutonniΈre deformities in the rheumatoid thumb. (23rd January 2014) - Toyama, S.; Oda, R.; Tokunaga, D.; Fujiwara, H.; Kobashi, H.; Yamazaki, T.; Okubo, N.; Kubo, T.
Abstract : Background: Among the thumb deformities observed in rheumatoid arthritis (RA), boutonnière deformities are the most common and account for 70% of all deformities present. However, it is difficult to determine the proper timing for interventions due to progressive limitations in range of motion (ROM) and instability of the thumb joints in these patients. Objectives: We hypothesized that ROM limitation above a certain level would result in functional hand deficiencies. In this study, we assessed the ROM and function of the thumb joint in patients having rheumatoid arthritis-related boutonnière deformities. Methods: This study included 50 thumbs with boutonnière deformities in 31 patients. Of the 50 thumbs, we were able to measure the ROM of 27 thumbs in 18 patients. The patients available for assessment (all females) had a mean age of 65.0 (range, 51 to 76) and a mean disease duration of 21.8 years (range, 14 to 33). The active and passive ROM at the metacarpophalangeal (MP) joint and interphalangeal (IP) joint was measured, and the differences between the active and passive ROM of each joint were calculated as an index for joint instability. Functional evaluations were completed according to the Disability of Arm, Shoulder and Hand (DASH) for upper limb function and modified Kapandji index (MKI) for finger function. Results: The average ROM at the MP joint was as follows; active flexion, 56.8 degrees (range, 0 to 90); passive flexion, 65.3 degrees (range, 0 to 100); active extension, -22.6 degrees. (range, -84 to 20); passive extension, -3.2 degree (range, -50 to 40). The average ROM at the IP joint was as follows; active flexion, 23.0 degrees (range, -84 to 70); passive flexion, 38.1 degrees (range, -70 to 86); active extension, 43.7 degrees (range, 0 to 90); passive extension, 59.1 degrees (range, 10 to 100). MP joint extension and IP joint flexion had strong correlations with functional evaluations. MP joint extension strongly correlates with IP joint flexion in both active and passive motion. ROM limitations progressed markedly when active MP joint extension became less than -30 degrees and active IP joint flexion became less than 30 degrees. Upper limb function deteriorated with a decrease of active extension at the MP joint, but the overall finger function markedly deteriorated when the active extension at the MP joint became less than -30 degrees. The upper limb function and the finger motion were deteriorating with the decrease of active flexion at the IP joint. Conclusions: Decreased finger extension mobility is reported to impact the working space in the hand, resulting in functional deficiencies. Boutonnière deformities result in functional deficiencies in the same manner, as a result of subluxation of the MP joint due to synovitis. Furthermore, boutonnière deformities result in hyperextension or joint instability at the IP joint and leads to deteriorating finger function. From the result of this study, active ROM at the MP joint less than -30 degrees impaired the mobility of the IP joint and destabilized the IP joint, resulting in huge impacts in activities of daily living. We considered that active ROM at the MP joint less than -30 degrees might be a threshold for therapeutic intervention. Disclosure of Interest: None Declared